Trait Mindfulness and Counterproductive Work Behavior: The Role of Stop and Start Control - Endang Parahyanti; Muhammad Rizky (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2022)
This study aimed to examine the antecedents of Counterproductive Work Behavior (CWB) by investigating two dimensions of self-control, namely stop and start control, as mediators between trait mindfulness and CWB. A correlational research design was employed, and the participants were full-time workers aged between 20 and 39 years. The instruments consisted of the Stop Control and Start Control Scale, Mindfulness Attention Awareness Scale (MAAS), and Counterproductive Work Behavior Checklist (CWB-C). The results of the mediation analysis showed that the trait mindfulness had an indirect effect on CWB through stop control (ab = -.11, p < .01) and start control (ab = -.04, p < .01), as well as a direct effect on CWB (c’ = -.07, p < .01; c’ = -.24, p < .01). These findings suggested that stop and start control partially mediated the relationship between trait mindfulness and CWB.